INVERSI FILTER Q UNTUK MENINGKATKAN FAKTOR KUALITAS DAN RESOLUSI DATA SEISMIK - , KHRISTIAN ENGGAR PAMUJI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Seismic waves travelling through media are attenuated by the conversion of elastic energy into heat. Upon being attenuated, the travelling wave changes: amplitude is reduced, travelling waveform is modified due to high-frequency content absorption, and phase is delayed. The effect of attenuation on seismic data can be reduced by applying inverse Q filter method. In this case study, Quality factor Q was determined by spectral ratio method, then it was used in inverse Q filter process. Synthetic seismic data generated by MATLAB (Seislab) program and real seismic data recording from NPRA (National Petroleum Reserve- Alaska) USGS Central Alaska was processed using this invers method. Using invers Q filter, quality factor of seismic data has improved. The value of Q improved from 176 to 984. Inverse method also increased resolution of seismic data.